Book Review. Issue 1 (1st April 2019) - Martin, Adrian
Realism in Greek Cinema: From the Post-War Period to the Present, Vrasidas Karalis (2017)London: I.B. Tauris, 304 pp., ISBN 978-1-78076-729-1, h/bk, £115